Evaluation of Clomiphene Citrate to Induce the Estrus in Bitches out of Breeding season. (Journal of Hama University, 2019)
In this study, twelve different bitches, whose ages varied between two and five years from different breeders, were used to evaluate their response to the use of Clomiphene Citrate (CC) for inducing the estrus out of the breeding season. Before starting the experiment, the bitches were examined by ultrasound and vaginal cytology to be sure that there is no estrus. Then, the bitches were divided randomly into two groups. In the first experimental group (G1, n=6) CC:(100 mg) anti estrogen analogue was given orally once a day and daily until ovulation occurred or up to 15 days. In the control group (G2, n=6), 10 ml physiological solution was given orally once a day at the time of CC dosages in the first experimental group. The estrus and the ovulation time for the two groups were determined by (vaginal cytology, progesterone concentrations, and ultrasound). Bitches that showed estrus signs were mated twice a day for the three days following the beginning of the estrus. Pregnancy was then examined by ultrasound after 20 and 35 days.Results showed a significant difference (P0.05) for the mean period of time required for estrus induction between the two groups (8.33 & 12) days respectively> There was also a significant difference (P0.05) in the proportion of the bitches that showed estrus between the two groups (3 & 1) respectively.These results indicate that using of CC (100mg, daily dose) for 15 days is not enough to Induce the estrus in bitches out of the breeding season.